Reinventing the globalization of sustainable university systems: A case study of current statue, challenges and guidelines in Thailand - Makul, Natt; Sokrai, Prakasit (International Journal of Psychosocial Rehabilitation, 2020)
Recently globalization of Thailand university has taken a diverse approach and increased its proactiveness to meet the international university standards. This article elucidates important transformation that is taking place on Thailand education systems it will also point out the nature of the Thailand university education system and then discuss Thailand university system sustainability especially in the quest in realization the extending demand for university studies both in the country and also globally. Among other important items that will be considered as the subject matter the impact of globalization of university education in Thailand will be given more emphasis. Furthermore, this research aims at pointing out a list of issues regarding the impact of globalization of university education in Thailand. It will also focus on various aspects that are attributed to Thailand educational sector. This aspect will be critically analyzed to get the inference to Thailand university educational system. The occurrence of the Thailand crisis resulted in a major breakdown of Thailand educational system, it also attributed to a decline in the general educational productivity within the country and should be integrated to the globalization across the entire policies areas to effectively streamline and improve globalization of the Thailand university education by Thailand as a nation.